The Influence Of Leader's Comprehension About The Church’s Mandate To The Implementation Of Vision Mission Of Indonesian Bethel Church In Surabaya - Yunita Stella (Theological Journal Kerugma, 2020)
This research concerns about the Influence of Leader’s Comprehension about the Church’s Mandate to the Implementation of Vision Mission of Indonesian Bethel Church in Surabaya. The results has shown that the Leader's Comprehension about the Church’s Mandate has a significant effect to the Implementation of Vision Mission of Indonesian Bethel Church in Surabaya. A slight reduction or addition of Leader's Comprehension about the Church’s Mandate will have a relatively large effect on reducing or increasing the Implementation of Vision Mission of Indonesian Bethel Church in Surabaya. The results of this research indicate that the Leader's Comprehension about the Church’s Mandate has an effect of 20.4% to the Implementation of Vision Mission of Indonesian Bethel Church in Surabaya.